2010
DOI: 10.1017/s1473550410000194
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemolysis of the Murchison meteorite: identification of oxygen bound and occluded units in the organic macromolecule

Abstract: An organic macromolecular residue, prepared from the Murchison meteorite by treatment with hydrofluoric and hydrochloric acids, was subjected to online thermochemolysis with tetramethylammonium hydroxide (TMAH). The most abundant compound released by thermochemolysis was benzoic acid. Other abundant compounds include methyl and dimethyl benzoic acids as well as methoxy benzoic acids. Short chain dicarboxylic acids (C 4-8 ) were also released from the organic macromolecule. Within the C 1 and C 2 benzoic acids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
(84 reference statements)
1
11
0
Order By: Relevance
“…Analyses of this sort have taken place on Allende (CV3) (Levy et al, 1970;Simmonds et al, 1969), Murchison (CM2) (Biemann, 1974;Holzer and Oró , 1977;Komiya and Shimoyama, 1996;Levy et al, 1973;Murae, 1995;Remusat et al, 2005;Sephton and Gilmour, 2001;Studier et al, 1972;Watson et al, 2010), Erakot (CM2), Essebi (CM2), Kivesvaara (CM2), Mighei (CM2), Murray (CM2), Nogoya (CM2) (Sephton et al, 2004a), Orgueil (CI1) (Bandurski and Nagy, 1976;Remusat et al, 2005), and a number of Antarctic carbonaceous chondrites (Kitajima et al, 2002;Komiya et al, 1993;Murae, 1995;Sephton et al, 2004a). The aromatic nature of macromolecular materials is readily evident during pyrolysis studies on meteorite samples that have been previously thermally extracted, solvent-extracted, or aciddemineralized.…”
Section: Aliphatic and Aromatic Unitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses of this sort have taken place on Allende (CV3) (Levy et al, 1970;Simmonds et al, 1969), Murchison (CM2) (Biemann, 1974;Holzer and Oró , 1977;Komiya and Shimoyama, 1996;Levy et al, 1973;Murae, 1995;Remusat et al, 2005;Sephton and Gilmour, 2001;Studier et al, 1972;Watson et al, 2010), Erakot (CM2), Essebi (CM2), Kivesvaara (CM2), Mighei (CM2), Murray (CM2), Nogoya (CM2) (Sephton et al, 2004a), Orgueil (CI1) (Bandurski and Nagy, 1976;Remusat et al, 2005), and a number of Antarctic carbonaceous chondrites (Kitajima et al, 2002;Komiya et al, 1993;Murae, 1995;Sephton et al, 2004a). The aromatic nature of macromolecular materials is readily evident during pyrolysis studies on meteorite samples that have been previously thermally extracted, solvent-extracted, or aciddemineralized.…”
Section: Aliphatic and Aromatic Unitsmentioning
confidence: 99%
“…Thermochemolysis has allowed the identification of numerous oxygencontaining units in meteorite macromolecular materials. Other compounds include benzene dicarboxylic acids, naphthalene carboxylic acids, and short-chain aliphatic acids (Remusat et al, 2005;Watson et al, 2010). Other compounds include benzene dicarboxylic acids, naphthalene carboxylic acids, and short-chain aliphatic acids (Remusat et al, 2005;Watson et al, 2010).…”
Section: Oxygen-containing Unitsmentioning
confidence: 99%
“…It is reasonable to expect these entities to be present in degradation products from the selective chemical cleavage of oxygen bound units. Yet data from thermochemolysis using tetramethylammmonium hydroxide do not reveal a preference for meta units when either sub-pyrolysis or pyrolysis temperatures are utilised (Watson et al, 2010).…”
Section: Macromolecular Origin Of Substituted Benzenesmentioning
confidence: 98%
“…Examples of on-line pyrolysis of macromolecular material in meteorites include direct insertion-mass spectrometry (Studier et al, 1972), pyrolysis-gas chromatography-mass spectrometry (Simmonds et al, 1969), pyrolysis-gas chromatography-isotope ratio-mass spectrometry (Sephton and Gilmour, 2001b), thermochemolysis-gas chromatography-mass spectrometry (Remusat et al, 2005;Watson et al, 2010) and pyrolysis-Fourier transform infrared spectroscopy Sephton, 2009a,b, 2011). On-line pyrolysis confers a number of advantages including analytical simplicity, the retention of volatiles and small sample size requirements.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 The MOM fraction of Murchison has also yielded aromatic acids as methyl derivatives after treatment with tetramethylammonium hydroxide (TMAH) and pyrolysis. 9 Meteorite organic matter is complex, and its origin is widely debated; however, it is largely accepted that a portion of the organic matter is presolar in origin (see ref 10 for a detailed review). Studies exposing polar ices to ultraviolet (UV) radiation have shown that it is possible to create both aromatic and aliphatic compounds resembling those found in meteorite organic matter, 11−15 although only small quantities of aromatic compounds were recorded by Nuevo et al 13 Other experiments using polycyclic aromatic hydrocarbons mixed with polar ices have yielded aromatic structures with functional groups, such as those found previously in meteorites, including carboxyl, methoxy, and aldehyde moieties.…”
Section: ■ Introductionmentioning
confidence: 99%